Impactful Social Media Utilization: Enhancing Brand Development and Consumer Satisfaction in Pontianak City’s Micro Businesses - Syarif Agussaid Alkadrie; Samsul Hidayat (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
This study aims to analyze the effect of social media use through consumer satisfaction on brand development in micro-businesses in Pontianak. Data were collected from 200 respondents who are owners or managers of micro-businesses in Pontianak. Data collection was conducted through questionnaires measuring the variables of social media usage, consumer satisfaction, and brand development. The results of the analysis showed a positive and significant relationship between social media usage and consumer satisfaction. In addition, consumer satisfaction was also shown to have a positive and significant effect on brand development. These findings indicates that micro-businesses that actively use social media and pay attention to consumer satisfaction tend to have better brand development. This results provide important implications for micro-business owners in planning brand development strategies through social media utilization and increased consumer satisfaction. In this digital era, the use of social media and positive interactions with consumers can be key factors in building and strengthening the brand of micro-businesses in Pontianak.